2014
DOI: 10.1016/j.jhsa.2014.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Hand Function and Quality of Life Before and After Fasciectomy for Dupuytren Contracture

Abstract: PurposeTo describe changes in joint motion, sensibility, and scar pliability and to investigate the patients' expectations, self-reported recovery, and satisfaction with hand function, disability, and quality of life after surgery and hand therapy for Dupuytren disease. MethodsThis prospective cohort study collected measurements before surgery and 3, 6, and 12 months after surgery and hand therapy. Ninety patients with total active extension deficits of 60 degrees or more from Dupuytren contracture were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 43 publications
0
51
0
5
Order By: Relevance
“…A recent prospective study of 90 patients treated with limited fasciectomy at a university hand surgery centre in Sweden, reported that at 1 year the mean AED for the MCP joints was 5 (SD 9) and for the PIP joints 22 (SD 18). 11 It is unclear whether the authors used 0°for hyperextension (as in our study) or used the actual values, which would underestimate the reported extension deficit. They reported that 81% were satisfied at 1 year.…”
Section: Discussionmentioning
confidence: 80%
“…A recent prospective study of 90 patients treated with limited fasciectomy at a university hand surgery centre in Sweden, reported that at 1 year the mean AED for the MCP joints was 5 (SD 9) and for the PIP joints 22 (SD 18). 11 It is unclear whether the authors used 0°for hyperextension (as in our study) or used the actual values, which would underestimate the reported extension deficit. They reported that 81% were satisfied at 1 year.…”
Section: Discussionmentioning
confidence: 80%
“…However, considerable attention has been paid for the non-operative treatment of Dupuytren disease. Injectible collagenase is more efficient than surgical fasciotomy and has milder side effects, which leads to higher patient satisfaction [97,98]. Studies on the influence of CHCs on Dupuytren's cords and on Dupuytren's disease fibroblasts have demonstrated that clostridial collagenases can efficiently digest ECM of Dupuytren's disease cords without inducing significant cytotoxicity or structural damage to non-collagenous tissue elements [99,100].…”
Section: Collagenase As Debriding Agent In Wound Healingmentioning
confidence: 99%
“…(19) The patients were invited to the study in the order they were scheduled for surgery thus forming a consecutive sample. Inclusion criteria for the cohort study were having DD in one or several fingers of digit II-V, with an extension deficit of 60° or more in an isolated finger joint (metacarpophalangeal (MCP) or proximal/distal interphalangeal (PIP and DIP) joint only) or throughout a whole finger (MCP, PIP, DIP together).…”
Section: Participantsmentioning
confidence: 99%
“…(16) Furthermore, DD leads to consequences such as activity limitations, safety and social issues of hand function and quality of life issues. (1,17,18,19) Higher DASH score has also shown to correlate with worse general health (20), but the association between DASH and quality of life outcomes after fasciectomy for DD has not been investigated previously.…”
Section: Introductionmentioning
confidence: 99%